2012
DOI: 10.4161/adip.20891
|View full text |Cite
|
Sign up to set email alerts
|

Role of adipose and hepatic atypical protein kinase C lambda (PKCλ) in the development of obesity and glucose intolerance

Abstract: PKCλ, an atypical member of the multifunctional protein kinase C family, has been implicated in the regulation of insulin-stimulated glucose transport and of the intracellular immune response. To further elucidate the role of this cellular regulator in diet-induced obesity and insulin resistance, we generated both liver (PKC-Alb) and adipose tissue (PKC-Ap2) specific knockout mice. Body weight, fat mass, food intake, glucose homeostasis and energy expenditure were evaluated in mice maintained on either chow or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(43 reference statements)
1
5
2
Order By: Relevance
“…It may be noted that AλKO mice, derived from the same line of PKC-λ-floxed mice used in our study, have also been studied by another group, 20 and, as in our study, were found to have normal glucose tolerance and a trend to diminished food intake. These AλKO mice were also found to have energy expenditure, respiratory quotients, and locomoter activity indistinguishable from that of wild-type mice 20 .…”
Section: Discussionsupporting
confidence: 72%
“…It may be noted that AλKO mice, derived from the same line of PKC-λ-floxed mice used in our study, have also been studied by another group, 20 and, as in our study, were found to have normal glucose tolerance and a trend to diminished food intake. These AλKO mice were also found to have energy expenditure, respiratory quotients, and locomoter activity indistinguishable from that of wild-type mice 20 .…”
Section: Discussionsupporting
confidence: 72%
“…aP2-Cre mice have been generated by at least four independent laboratories and widely used in studies targeting adipose tissue in vivo [30] that resulted in seminal findings about the adipose-tissue specific roles of several key genes, including the insulin receptor (FIRKO mouse), Glut4 , PKC λ, etc. [1] , [6] , [19] , [30] , [52] . Over the past few years, studies have reported the observations of aP2-Cre activity in other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cholesterol levels were determined using the Infinity cholesterol kit (Thermo Scientific Inc., Rockford, IL) as described (16). An intraperitoneal pyruvate tolerance test was conducted by injection of sodium pyruvate (2 g/kg; Sigma-Aldrich, St. Louis, MO) in 0.9% w/v NaCl, as described previously (17). Tail blood glucose levels (milligrams per deciliter) were measured with a TheraSense Freestyle glucometer (Abbott Diabetes Care, Inc., Alameda, CA) before (0 min) and at 15, 30, 45, 60, and 120 min after injection.…”
Section: Biochemical Assaysmentioning
confidence: 99%